Conditional Regulation of Blood Pressure in Response to Emotional Stimuli by the Central Nucleus of the Amygdala in Rats - Yamanaka, Ko; Waki, Hidefumi (Frontiers in Physiology, 2022)
Humans and animals can determine whether a situation is favorable to them and act accordingly. For this, the autonomic tuning of the cardiovascular system to supply energy to active skeletal muscles through the circulatory system is as important as motor control. However, how the autonomic cardiovascular responses are regulated in dynamically changing environments and the neuronal mechanisms underlying these responses remain unclear. To resolve these issues, we recorded the blood pressure and heart rate of head-restrained rats during dynamically changing appetitive and aversive classical conditioning tasks. Rats learned various associations between conditioned stimuli and unconditioned stimuli in appetitive (sucrose water), neutral (no outcome), and aversive (air puff) blocks. Blood pressure and heart rate in the appetitive block gradually increased in response to the reward-predicting cue and the response to the actual reward vigorously increased. The reward-predictive response was significantly higher than the responses obtained in the neutral and aversive condition blocks. To investigate whether the reward-predictive pressor response was caused by orofacial movements such as an anticipatory licking behavior, we analyzed separately high- and low- licking trials. The conditioned pressor response was observed even in trials with low-licking behaviors. Blood pressure and heart rate responses to the air puff-predicting cue in the aversive block were not significantly different from the responses in the neutral block. The conditioned blood pressure response rapidly changed with condition block switching. Furthermore, to examine the contribution of the amygdala as an emotion center to these conditioned responses, we bilaterally microinjected a GABAA receptor agonist, muscimol, into the central nucleus of the amygdala. Pharmacological inactivation of the central nucleus of the amygdala significantly decreased the reward-predictive pressor responses. These results suggest that blood pressure is adaptively and rapidly regulated by emotional conditioned stimuli and that the central nucleus of the amygdala participates in regulating pressor response in dynamically changing situations.